A Case Series Of Arthritis In Hansen’s Disease - Hendra Gunawan; Deasy Natalia Adriana; Awalia Awalia; Joewono Soeroso (Biomolecular and Health Science Journal, 2020)
Hansen’s disease or leprosy is a chronic granulomatous infectious disease caused by Mycobacterium leprae. Musculoskeletal complaints might be the initial presentation of patients with Hansen’s disease. Symptoms are common with clinical spectrum ranging from mild to debilitating arthritis.  Regarding its wide clinical spectrum, a history taking especially in an endemic area like Indonesia on the possibility of Hansen’s disease cannot be ruled out in patients with arthritis. We reported 3 cases of arthritis in Hansen’s disease. First case was a 62-year-old Javanese female who had a deformity and chronic poly symmetry arthritis. Second case was a 45-year-old Javanese male with chronic bilateral knee pain as initial presentation of Hansen’s disease and the last case was 61-year-old Javanese male who had acute bilateral knee pain with erythematous maculae associated with Erythema Nodosum Leprosum. All cases responded to corticosteroid 1 mg/BW/day.